PENINGKATAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN GEOMETRI PYTHAGORAS MELALUI ANALISIS PROBLEMATIKA DAN STRATEGI PERBAIKAN PEMBELAJARAN - Adillia Natasya Saputri; Abi Suwito; Frenza Fairuz Firmansyah; Susanto (EDUCATIONAL JOURNAL : General and Specific Research, 2026)
This study aims to analyze the various problems experienced by students in learning geometry and to examine improvement efforts that can enhance students’ learning motivation. Based on the results of the study, it was found that many students experience difficulties in understanding basic geometry concepts. These difficulties are reflected in students’ low ability to recognize shapes, understand relationships between geometric figures, and apply formulas correctly in problem-solving. In addition, students often make errors in using principles and procedures for solving geometry problems. Another dominant difficulty is students’ limited ability to understand word problems, which makes it difficult for them to translate problems into mathematical forms. The factors causing these learning difficulties originate not only from cognitive aspects, but are also influenced by emotional factors, the learning environment, and students’ low motivation in participating in the learning process. Therefore, effective improvement efforts are needed, such as strengthening mathematical communication, implementing active learning methods, and providing opportunities for students to explore and express mathematical ideas independently. With appropriate and engaging learning strategies, students’ learning motivation can increase, leading to a better understanding of geometry concepts and improved learning outcomes.